A Critical Review on the Impact of Azo Textile Wastewater in Wet Fabric Industries on The Receiving Water Bodies and Aquatic Living - HASSAN, SITI NUR FATINAH; Ab.Aziz, Nur Adila (Recent Trends in Civil Engineering and Built Environment, 2022)
The textile industry is high pollution country. The wet fabric industry generated wastewater while solid waste is generated in the dye fabric industry. Azo dye is a common synthetic organic dye used and has high toxicity compared to other dyes. This study aims to identify the families of azo dye and its characteristics using in the wet fabrics industries simultaneously to review the impacts of azo dye wastewater on the water bodies and aquatic living based on the previous studies and how to treat the effluent. There have been processes from identifying problem statements for data collection, choosing journals or materials until data collection. Based on the findings, the azo dye has to produce colourless aromatic amines (AAs) produced via anaerobic azo bond-breaking. AAs are available in different forms, from the simplest with one Amino group to the most complicated with numerous aromatic rings. AAs are a major category of water contaminants since they are very toxic and carcinogenic.Based on European Commission and Registration, Evaluation, Athorisation and Restriction of Chemicals, REACH regulation, produce databases list of AAs prohibited, 1A and 1B. Many prohibited AAs should category in 1A and 1B, but there is a lack of sufficient and comprehensive data because they import textiles from Asian countries. AAs and wet fabric processes emit extremely polluting effluent that, if not properly treated, will harm water bodies and aquatic life. There are several wastewater treatment options, each with its own set of benefits and drawbacks that should be considered in terms of efficiency, effectiveness, cost, and environmental impact. Biological wastewater treatment has certain advantages over other chemical and physical treatments, according to the study.